1978
DOI: 10.1111/j.1432-1033.1978.tb12785.x
|View full text |Cite
|
Sign up to set email alerts
|

RNA Hybridization to DNA Coupled with Cyanogen‐Bromide‐Activated Sephadex

Abstract: A method for purifying RNA by hybridization to complementary DNA immobilized on Sephadex is described and is illustrated by the purification of polyoma mRNA. Denatured DNA can be immobilized on cyanogen-bromide-activated Sephadex whilst remaining freely available for hybridization. However, after activation with cyanogen bromide, followed by the coupling of DNA and deactivation with ethanolamine, Sephadex acts as an ion-exchange resin. It is therefore necessary to elute RNA from DNA-Sephadex by a combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…LSU and its mRNA are both detectable in dark-grown plants, as studies on protein synthesis in isolated etioplasts would indicate [38]. However, whereas the mRNA level increases markedly in the first 12 hr of illumination, the LSU itself remains at a low level for about 24 hr and only then accumulates rapidly.…”
Section: Resultsmentioning
confidence: 98%
“…LSU and its mRNA are both detectable in dark-grown plants, as studies on protein synthesis in isolated etioplasts would indicate [38]. However, whereas the mRNA level increases markedly in the first 12 hr of illumination, the LSU itself remains at a low level for about 24 hr and only then accumulates rapidly.…”
Section: Resultsmentioning
confidence: 98%
“…Hybridized nucleic acids can easily be eluted from DPTE-materials by water or 99% formamide in analogy to DBM-cellulose (6). In contrast, supports synthesized by cyanogen bromide activation carry positively charged groups, requiring elution in the presence of moderate salt concentration (5). A couple of hybridization selection reactions with macroporous DPTE S-500 have shown that unspecific adsorption of nucleic acids is even lower than for G-25 materials.…”
Section: Discussionmentioning
confidence: 99%
“…E.coli-DNA sheared or sonicated (see above) was either dissolved in 0.1 ml 0.2 M MES pH 8.0, boiled, cooled, and mixed with 0.9 ml formamide (5) or dissolved in 1 ml 10 mM potassium phosphate pH 8.0, boiled and stored on ice immediately before use (6). The reaction mixture was maintained at 4°C (5) or at room temperature (6) overnight. Between 1 and 2 mg/ml of DNA was used for coupling to Cl-2B, Cl-6B, S-500 and S-1000 in contrast to about 0.1-0.3 mg/ml in the case of G-25 superfine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional mapping was performed as Coronavirus tryptic peptide fingerprints o~. described by Siddell (1978) with the separation of peptides on thin layer cellulose plates (Eastman Kodak Sheet 13255) by electrophoresis in pH 2.1 buffer and ascending chromatography in butanol-acetic acid-water-pyridine. The plates were dried, in some cases after dipping in 7 % (w/v) PPO (2,5-diphenyloxazole) dissolved in ether, and exposed to Fuji RX film at room temperature or at -7 0 °C as appropriate.…”
Section: Methodsmentioning
confidence: 99%